Strategies of Helicobacter pylori in evading host innate and adaptive immunity: insights and prospects for therapeutic targeting - Fan, Jiawei; Zhu, Jianshu; Xu, Hong (Frontiers in Cellular and Infection Microbiology, 2024)
Helicobacter pylori (H. pylori) is the predominant pathogen causing chronic gastric mucosal infections globally. During the period from 2011 to 2022, the global prevalence of H. pylori infection was estimated at 43.1%, while in China, it was slightly higher at approximately 44.2%. Persistent colonization by H. pylori can lead to gastritis, peptic ulcers, and malignancies such as mucosa-associated lymphoid tissue (MALT) lymphomas and gastric adenocarcinomas. Despite eliciting robust immune responses from the host, H. pylori thrives in the gastric mucosa by modulating host immunity, particularly by altering the functions of innate and adaptive immune cells, and dampening inflammatory responses adverse to its survival, posing challenges to clinical management. The interaction between H. pylori and host immune defenses is intricate, involving evasion of host recognition by modifying surface molecules, manipulating macrophage functionality, and modulating T cell responses to evade immune surveillance. This review analyzes the immunopathogenic and immune evasion mechanisms of H. pylori, underscoring the importance of identifying new therapeutic targets and developing effective treatment strategies, and discusses how the development of vaccines against H. pylori offers new hope for eradicating such infections.